Strategies to Preserve Postharvest Quality of Horticultural Crops and Superficial Scald Control: From Diphenylamine Antioxidant Usage to More Recent Approaches - Cindy Dias; Ana L. Amaro; Ângelo C. Salvador; Armando J. D. Silvestre; Sílvia M. Rocha; Nélson Isidoro; Manuela Pintado (MDPI AG, 2020)
Horticultural crops are vulnerable to several disorders, which affect their physiological and organoleptic quality. For about forty years, the control of physiological disorders (such as superficial scald) in horticultural crops, particularly in fruit, was achieved through the application of the antioxidant diphenylamine (DPA), usually combined with controlled atmosphere (CA) conditions. However, identification of DPA residues and metabolites in treated fruits, associated with their toxicity, banned the use of this antioxidant in Europe. This triggered the urgent need for novel and, ideally, natural and sustainable alternatives, combined with adequate storage conditions to protect cultivars from harmful agents. This review systematizes the state-of-the-art DPA application on several fresh cultivars, such as apples, pears, and vegetables (potatoes, spinach, etc.), as well as the possible mechanisms of the action and effects of DPA, emphasizing its antioxidant properties. Alternative methods to DPA are also discussed, as well as respective effects and limitations. Recent research on scald development molecular pathways are highlighted to open new non-chemical strategies opportunities. This appraisal shows that most of the current solutions have not lead to satisfactory commercial results; thus, further research aimed to understand the mechanisms underlying postharvest disorders and to design sustainable and safe solutions to improve horticultural products storage is needed.